Study on Natural Circulation Heat Transfer Characteristics of Different Liquid Metals Based on Factor Analysis - Xiang, Feng; Tao, Zhou; Jialei, Zhang; Boya, Zhang; Juan, Chen (Frontiers in Energy Research, 2020)
The study of the commonness and differences of natural circulation of different liquid metals plays an important role in improving the safety of reactors. The numerical simulation of liquid metal natural circulation heat transfer was carried out by CFX, and its heat transfer coefficient, flow, and outlet temperature were studied. The factor analysis method was used to analyze the influence of the interaction between factors and the contribution rate of each factor. It can be found that the commonality of heat exchange between different liquid metals is that the heat transfer coefficient is mainly affected by the power, the contribution rate of power to the heat transfer coefficients of liquid sodium, sodium-potassium alloy, lead, and lead-bismuth alloy reached 40.16, 78.16, 97.95, and 92.19%, respectively; the flow rate and outlet temperature of the liquid metal increase with the increase of power; the flow rate and outlet temperature are hardly affected by pressure. The difference is that the heat transfer coefficients of liquid metals have different trends with the change of power; in addition, the interaction between the factors of heat transfer coefficient is different; the heat transfer coefficient of liquid sodium and sodium-potassium alloy is affected by pressure, the pressure affects the heat transfer coefficient by coupling with power or inlet temperature. In general, the heat transfer performance of sodium is the best, with a much higher heat transfer coefficient than the other three liquid metals; the natural circulation ability of sodium-potassium alloy is the strongest, and its flow velocity is greater than other liquid metals.